A The Use of Animation Movie in Teaching Writing of Narrative Text - Reza, Putri Alia (Native: Journal of English Teaching and Learning, 2023)
The objectives of this research are to find out how to use animation movies in teaching writing of narrative text and to analyze students’ responses toward the use of animation movies in teaching writing of narrative text. This research was conducted at SMA Muhammadiyah 5 Rancaekek academic year 2021/2022. The participants of the study were the English teacher and the students of X IIS which consisted of 21 students. This research used a qualitative method. For the data collection, the researcher uses observation, survey questionnaires, and instruments. Animation movies could be used as a medium in teaching the writing of narrative text. As a result, the animation movie helped the students to discover various ideas to write and made the teaching-learning process more effective. Most students did not feel bored in the teaching-learning process, could understand the material easily, and were inspired to write with various ideas.